مسألة تزاحم الأحكام في تقييم الشخصيات لدى ابن تيمية - بليل عبد الكريم (International Institute of Islamic Thought, 2014)
تهدف هذه الدراسة إلى فهم مسألة "تزاحم الأحكام" حال توارد الخيريْنِ وازدحام الشرَّيْنِ في زمن واحد على معين واحد. وهي من مسائل الفقه النادرة التي، امتاز بها الشرع الإسلامي، فأكسبته مرونة وصلابة في النظر إلى النوازل المكانية والزمانية في الأفراد والجماعات. وقليل من الباحثين من سبر أغوار هذا الموضوع، لأنه صعب على غير أولي النهى من مثل ابن تيمية، الذي أعمل قاعدة التزاحم في العمليات والعلميات، وأعمل القاعدة في تقييم الأشخاص والعلوم. ومع أن دفاع ابن تيمية عن التوحيد الخالص والعقيدة الصافية أمر معروف، لكن، قَلَّ مَنْ بيَّن منهجَه في النقد، وأبرز تعاملَه بقاعدة الموازنة التي يقتضيها تزاحم الأحكام في نقد الفرد المـُعيَّن، أو الجماعة المـُعيَّنة. This study aims to understand the issue of judgments rivalry when two goods and two evils come on one issue at the same time. It is a unique issue, which has characterized Islamic law, and gave it flexibility and rigor in looking at the emerging issues in time and space, whether regarding individuals or groups. Few people have studied this issue, as it is a difficult one expect for those thinkers like Ibn Taymiyyah who applied the rule of rivalry in the academic and theoretical aspects, and also in evaluating individuals and disciplines. Although his defense of straight tawhid and pure cread is well known, but very few have illustrated his methodology of criticism, and uncover his approach in dealing with the balance needed to settle the rivalry of judgments, regarding a certain individual or certain group.